A TaqMan qPCR for precise detection and quantification of diarrheagenic Escherichia coli - Bingyu Xue; Huanrong Zhang; Xia Yan; Xiaoyan Su; Yuling Zhou; Junjin Xie; Sheng Li; Yang Zhou; Lin Li (Scientific Reports)
Abstract Diarrheagenic Escherichia coli (DEC) are strains of Escherichia coli (E. coli) that can induce diarrhea symptoms in the host, as well as cause disease through contaminated food. To accurately and efficiently identify the five DEC types, this study retrieved the corresponding gene sequences from NCBI based on the virulence genes specified in Chinese national standards: invE, stx1, stx2, sth, stp, lt, aggR, astA, pic, bfpB, and escV. Probes and primers were designed for the conserved regions of these genes, and the amplification system, temperature, and other parameters were optimized. A TaqMan®single-plex real-time PCR assay was established for simultaneous detection of Enteropathogenic E. coli, Enteroinvasive E. coli, Enterotoxigenic E. coli, Enterohemorrhagic E. coli, and Enteroaggregative E. coli. The results demonstrated that the minimum detection limit for bacterial genomic DNA was 1.60 × 101 copies/μL (except for stx2 which was 1.60 × 102 copies/μL). The within-group variation rate ranged from 0.12 to 0.88%, while the between-group variation rate ranged from 0.67 to 1.62%. Moreover, R2 values for the standard curve generated by this method were between 0.999 and 1 with an amplification efficiency ranging from 98.4 to 100%. We evaluated a total of 122 clinical specimens using both conventional PCR and the qPCR method developed in this study. The findings indicated that the qPCR method exhibited high accuracy. Therefore, this study successfully developed a Taqman real-time fluorescence quantitative PCR assay with high specificity, sensitivity, repeatability, and amplification efficiency as well as significant regression effect. This assay can be utilized for clinical detection of DEC.